2007
DOI: 10.1016/j.vaccine.2006.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with non-replicating E. coli minicells delivering both protein antigen and DNA protects mice from lethal challenge with lymphocytic choriomeningitis virus

Abstract: In the midst of new investigations into the mechanisms of both delivery and protection of new vaccines and vaccine carriers, it has become clear that immunization with delivery mechanisms that do not involve living, replicating organisms are vastly preferred. In this report, non-replicating bacterial minicells simultaneously co-delivering the nucleoprotein (NP) of lymphocytic choriomeningitis virus (LCMV) and the corresponding DNA vaccine were tested for the ability to generate protective cellular immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…At least eight weeks following the last immunization or infection, mice were challenged with a 20XLD 50 dose of LCMV Armstrong by the i.c. route, a dose at which protection in the LCMV model has been commonly assessed [21, 37, 40, 42, 45]. Figure 4 displays the data from the challenge study and survival statistics are shown for each group of mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At least eight weeks following the last immunization or infection, mice were challenged with a 20XLD 50 dose of LCMV Armstrong by the i.c. route, a dose at which protection in the LCMV model has been commonly assessed [21, 37, 40, 42, 45]. Figure 4 displays the data from the challenge study and survival statistics are shown for each group of mice.…”
Section: Resultsmentioning
confidence: 99%
“…For lethal challenge studies, mice were challenged i.c. with 20XLD 50 of LCMV Armstrong as previously described [21, 37, 40, 42, 45] in 30 μl of virus diluent (PBS with 20% FBS and 1X Anti-Anti (Invitrogen, Carlsbad, CA)). Mice were observed daily for 16 days, a time point known to be adequate in the LCMV i.c.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minicells keep the rigid cell wall structure of 20 kinds of lipopolysaccharide like their parental bacteria [119]. The pathogen strains could produce minicells applied to vaccine but not complete safe for patient compared to lactic acid bacteria strains [120]. Therefore, minicells generated by lactic acid bacteria that are probiotic strain should be more interesting than others.…”
Section: Nanosized Delivery Generated By Microorganismsmentioning
confidence: 99%
“…The polysaccharides associated with the bacterial cell walls and the extracellular polysaccharides of lactic acid bacteria are either neutral or acidic [120,121]. There are abundance polysaccharides at the outer surface of the cell wall and extracellular.…”
Section: Nanosized Delivery Generated By Microorganismsmentioning
confidence: 99%